Translation Control of HAC1 by Regulation of Splicing in Saccharomyces cerevisiae - Xia, Xuhua (Université d'Ottawa | University of Ottawa, 2019)
Hac1p is a key transcription factor regulating the unfolded protein response (UPR) induced by abnormal accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) in Saccharomyces cerevisiae. The accumulation of unfolded/misfolded proteins is sensed by protein Ire1p, which then undergoes trans-autophosphorylation and oligomerization into discrete foci on the ER membrane. HAC1 pre-mRNA, which is exported to the cytoplasm but is blocked from translation by its intron sequence looping back to its 5'UTR to form base-pair interaction, is transported to the Ire1p foci to be spliced, guided by a cis-acting bipartite element at its 3'UTR (3'BE). Spliced HAC1 mRNA can be efficiently translated. The resulting Hac1p enters the nucleus and activates, together with coactivators, a large number of genes encoding proteins such as protein chaperones to restore and maintain ER homeostasis and secretary protein quality control. This review details the translation regulation of Hac1p production, mediated by the nonconventional splicing, in the broad context of translation control and summarizes the evolution and diversification of the UPR signaling pathway among fungal, metazoan and plant lineages.
Keywords: ER stress; ERN1; HAC1; IRE1; UPR; XBP1; non-spliceosome splicing; unfolded protein response; Base Sequence; Basic-Leucine Zipper Transcription Factors; Introns; Membrane Glycoproteins; Models, Biological; Protein Binding; Protein Biosynthesis; Protein-Serine-Threonine Kinases; RNA, Messenger; Repressor Proteins; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Signal Transduction; Unfolded Protein Response; Gene Expression Regulation, Fungal; RNA Splicing